THE USE OF INFORMATION AND COMMUNICATION TECHNOLOGY (ICT) DEVICES FOR TEACHING ENGLISH BY PRE-SERVICE TEACHERS - Andri Donal; Rivi Antoni; Evi Kasyulit (Jurnal Perspektif Pendidikan, 2019)
The use of ICT devices for teaching English is much needed right now, because it can attract students’ motivation in learning. It is very helpful especially for pre-service teachers, the novice teachers. The aims of this research were to investigate the use of ICT devices for teaching English by Pre-service teachers, describe the ICT devices frequently used for teaching English by pre-service teachers, find out students’ perceptions towards the use of ICT devices for teaching English by pre-service teachers. This research was employed through a mixed-methods approach that integrated qualitative and quantitative research design. The data handled quantitatively were gathered via the online questionnaire, and qualitative data were collected via the semi-structured interviews and observation to the 24 pre-service teachers. The result of research showed that there were three ways in using ICT devices in teaching English during teaching practice program. First, most of pre-service teachers always used ICT devices as the source of teaching material. Second, most of them often used ICT devices as the instructional teaching. The last most of pre-service teachers always used ICT devices as the communication tools. The ICT devices frequently used during teaching English were smartphone, computer, and in focus. Most students absolutely agree if pre-services teachers use ICT devices for teaching English because it was advantageous toward students’ English competences. It can be concluded that there were three ways of pre-service teachers used ICT devices during teaching practice program; mostly as the source of teaching materials, as the instructional teaching, and as the communication tools. Three ICT devices frequently used by pre-service teachers during teaching practice program were smartphone, computer, and in focus. Students absolutely agree towards the use of ICT devices by pre-service teachers in teaching English.